PENGARUH KOMBINASI GELLING AGENT CARBOPOL 934 DAN NATRIUM CARBOXYMETHYLCELLULOSE (Na-CMC) TERHADAP STABILITAS FISIK GEL GETAH JARAK PAGAR (Jatropha curcas) SEBAGAI PENYEMBUH LUKA INSISI - ari budi santoso (Universitas Duta Bangsa Surakarta, 2022)
Background: Jatropha sap (Jatropha curcas) is one of the herbal plants that contain tannins and saponins which are responsible for wound healing. Purpose: This study aims to determine the effect of the combination of Carbopol 934 and Na-CMC as a gelling agent on the physical stability of Jatropha curcas (Jatropha curcas) latex as a wound healing agent. Method: The method used in this study was to compare the combination of carbopol 934 and Na-CMC with different concentrations in the three formulations. The concentration used is 1%:4%, 1.5%:3,5% and 2%:3%. The three formulations will be tested for physical quality and tested for physical stability for 4 weeks. Then the formulation will be tested for primary irritation and incision wound healing test. Result: The results of the study showed that formulation I with a concentration of 1%:4% had a good physical quality test based on the results of tests carried out according to standards. Based on the results of the physical stability test, it showed stable adhesion results, while the pH, dispersibility and viscosity tests showed a change in storage for 4 weeks. Jatropha (Jatropha curcas) latex gel formulation did not cause primary irritation to rabbits. The three formulations have the ability to heal fast wounds on the 9th day.